Direzionalità e Condensazione del movimento corporeo attraverso uno strumento di auto-valutazione - 1 Sara Diamare, 2 Anna Ferrara, 3 Olimpia Ricciardi, 3 Simona Verniti (Marp Edizioni, 2020)
Movement can provide information about the way people express themselves and interacting with others. Scientific studies support the importance of non- verbal communication in the interpersonal relationship, decoding them through a reading of the body and of the movement. The aim of this research is to evaluate the reliability of an instrument of self-observation to investigate the expressiveness of the movement through specific dimensions, such as movement's chinesfera, centrality, structuring, rhythm, coordination, flow, rigidity and intensity. It is about the Scheda Diade, revision 3 di Lettura del Movimento, a tool for monitoring a conscious interaction, in which the subjects give self-assessment of one's motor and relational controtransfert. The instrument and the method of administration are based on constructs derived from neurophysiology and they are rooted in the analysis character's of W. Reich and in the Laban Movement Analysis. The study has been carried out on a sample of 432 subjects, included students, manager, teachers and counselors, who participated in training courses about the relationship with the other, through body awareness and Dance Movement Therapy modules. The collected data from the administration ex ante and ex post of the Scheda Diade revision 3 allowed to detect some changes in movement statistically significant, but not the subject of this discussion. From the intrinsic analysis of the test, subject of this study, emerged that the Scheda Diade revision 3 elicits the presence of two peculiar movement's components: Directionality and Condensation, that recall the archetypes of "male" and "female", not related to gender difference, but to modulation of motor expression. Factor analysis showed construct validity of the Scheda Diade revision 3.